"I didn't want to do it on my own": A qualitative study of women's perceptions of facilitating and risk factors for weight control on a UK commercial community program. (1st October 2021) - Hugh-Jones, Siobhan; Burke, Shaunna; Stubbs, James
Abstract: Overweight and obesity remain serious public health concerns. Outcomes from community based commercial weight management programmes vary, relapse is common and drop out is high. Outcomes could be improved by better understanding experiences on these programmes. The aim of our study was to generate accounts of people's experience on a commercial weight-management program to identify what experiences were perceived as facilitating, and what posed risks, to programme effectiveness and compliance. We conducted individual, semi-structured interviews with eighteen Caucasian women (mean age 45.4y) who were members of nation-wide UK commercial, fee-paying, community weight management programme. Interview data was analysed via framework analysis. Participants' experiences indicated that the programme helped by triggering several intra- and interpersonal processes that catalysed change across psychological, physiological, dietary and behavioural areas of their life. Risks to program adherence and effectiveness spanned well-known risks such as self-regulation fatigue and the difficulty of recovering from negative self-criticism, as well as new factors such as the confusing nature of weight change, the relatively powerful impact of everyday events, and the difficulty in getting the balance right between personalised support vs. intrusion. The complexity of reported experiences challenges the linear, predictive pathways of change proposed by many health behaviour models of weight management. To improve effectiveness, programmes need to go well beyond behavioural and dietary support. It is recommended that community, commercial programmes educate people about the physiological and psychological tensions they will encounter, why people lose weight at different rates, the likelihood of weight relapse and strategies to manage these, including evidence-based support for managing self-criticism.